2016
DOI: 10.3346/jkms.2016.31.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage Rate according to the Pulmonary Function of Korean Adults Aged 40 Years and Over: Analysis of the Fifth Korean National Health and Nutrition Examination Survey

Abstract: Influenza vaccination is an effective strategy to reduce morbidity and mortality, particularly for those who have decreased lung functions. This study was to identify the factors that affect vaccination coverage according to the results of pulmonary function tests depending on the age. In this cross-sectional study, data were obtained from 3,224 adults over the age of 40 who participated in the fifth National Health and Nutrition Examination Survey and underwent pulmonary function testing in 2012. To identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…In our study, less than 1 percent of individuals received an influenza vaccine, which is far lower than in other countries, many of which provide free vaccine through government-sponsored or private insurance programs. Similar studies have shown higher influenza vaccination coverage in the United [38], and Hong Kong (39%, over 65 years, 2015) [35]. Our findings were relatively consistent with prior studies in China showing an average national vaccination coverage ranging between 1.5% and 2.2% in 2004 and 2014 [22].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, less than 1 percent of individuals received an influenza vaccine, which is far lower than in other countries, many of which provide free vaccine through government-sponsored or private insurance programs. Similar studies have shown higher influenza vaccination coverage in the United [38], and Hong Kong (39%, over 65 years, 2015) [35]. Our findings were relatively consistent with prior studies in China showing an average national vaccination coverage ranging between 1.5% and 2.2% in 2004 and 2014 [22].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, less than 1% of individuals received an influenza vaccine, which is far lower than in other countries, many of which provide free vaccine through government-sponsored or private insurance programs. Similar studies have shown higher influenza vaccination coverage in the United States (43.5%, among adults over 19 years, 2015/16 season) [33], UK (56.0%, chronic disease patients, 2007/08 season) [37], Poland (11.1%, chronic disease patients, 2007/08 season) [37], Korea (45.2%, over 40 years, 2012) [38], and Hong Kong (39%, over 65 years, 2015) [35]. Our findings were relatively consistent with prior studies in China showing an average national vaccination coverage ranging between 1.5 and 2.2% in 2004 and 2014 [22].…”
Section: Discussionmentioning
confidence: 70%
“…In our study, less than 1 percent of individuals received an influenza vaccine, which is far lower than in other countries, many of which provide free vaccine through government-sponsored or private insurance programs. Similar studies have shown higher influenza vaccination coverage in the United States (43.5%, among adults over 19 years, 2015/16 season) [33], UK (56.0%, chronic disease patients, 2007/08 season) [37], Poland (11.1%, chronic disease patients, 2007/08 season) [37], Korea (45.2%, over 40 years, 2012) [38], and Hong Kong (39%, over 65 years, 2015) [35]. Our findings were relatively consistent with prior studies in China showing an average national vaccination coverage ranging between 1.5% and 2.2% in 2004 and 2014 [22].…”
Section: Discussionmentioning
confidence: 70%